Anomalous concentrations and environmental implications of rare earth elements in the rock-soil-moss system in the black shale area. (November 2022) - Xu, Yiyuan; Luo, Chaokun; Gao, Lei; Long, Jie; Xu, Hai; Yang, Ruidong
Abstract: Nowadays, rare earth elements (REEs) pollution caused by anthropogenic activities has aroused great attention, but the contribution of natural geological sources remains unclear. In this study, parent rocks, corresponding soil, and overlying moss ( Pohlia flexuosa Harv. In Hook) were collected to identify the release, transportation, and environmental exposure of REEs in the black shale areas. The results showed that black shales had elevated REEs levels (245 ± 124 mg kg −1 ) and served as a geogenic source of REEs. The released REEs were temporarily enriched in the acidized soil (327 ± 91.8 mg kg −1, pH 4.87 ± 0.810) and were still highly bioavailable, thereby resulting in REEs accumulated up to a high level in moss P. flexuosa (86.2 ± 64.3 mg kg −1 ). Hence, the ecological risks of REEs in black shale areas were assuredly enhanced. The shale-normalized results of REEs concentrations in the parent rock - soil - moss system followed a remarkably identical pattern and were characterized by strong enrichment in HREEs (LaN /YbN 0.520 ± 0.274), indicating that geogenic input was responsible for the concentration and composition of REEs in mosses. Moreover, REEs were readily preserved and not easily fractionated in moss P. flexuosa due to its special morphological features, indicating the lithological signatures of REEs in black shales were readily inherited by moss P. flexuosa, and underwent only minor losses. Overall, moss P. flexuosa could be used as a powerful tool to reflect the content and composition of REEs in black shale areas. Graphical abstract: Image 1 Highlights: Black shales have elevated REEs concentration and act as a geogenic source of REEs. REEs temporarily reserve in acidized soil substrate and is highly phytoavailable. Soils overlying black shale are responsible for the high moss REEs enrichment. HREEs enrichment with high fractionation degree is found in the rock-soil-moss system. Moss P. flexuosa is a robust biomonitor of REEs pollution in black shale areas.